Peran Oikumene : Menjalin Perdamaian Lintas Gereja - Trinitas Nuryani Dakhi (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Ecumenicalism, which comes from Greek meaning "one house," reflects the spirit of living together among Christians from different church traditions. This movement aims to establish peace and unite various denominations through dialogue, cooperation and communication based on the love of Christ. Ecumenicalism encourages churches to understand each other, collaborate, and reduce conflict without imposing doctrinal uniformity. Thus, through cooperation between denominations and inclusive forums, Ecumenical helps create a society that is harmonious, just, and oriented towards unity and shared peace.